Environmental and Nutritional Factors Associated with Inflammatory Bowel Disease: A Multi-Center Study in Vietnam - Viet Hang, Dao; Long, Dao Van; Ky, Thai Doan; Nga, Dinh Thi; Huy, Tran Van; Hoang, Bui Huu; Luan, Dang Minh; Van, Pham Thanh; Thuong, Nguyen Thu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Inflammatory bowel disease (IBD) is increasing in Asia, including Vietnam. However, epidemiological data in Vietnam remain limited, particularly regarding environmental and nutritional factors associated with IBD. This cross-sectional, multicenter study is part of the GIVES-21 project conducted across 24 countries. In Vietnam, five medical centers participated between October 2021 and October 2023. A total of 86 newly diagnosed IBD patients and 172 healthy controls were recruited. Data on living environment and dietary habits were collected. Univariable and multivariable logistic regression analyses were performed to identify factors associated with IBD. Analytical results revealed that associations with IBD included history of smoking (OR=12.4; CI: 1.5 – 105.1), vitamin intake (OR=3.9; CI: 1.3 – 11.9), living with a smoker (OR=0.2; CI: 0.1 – 0.5), rare (OR=0.1; CI: 0.02 – 0.8) or occasional (OR=0.1; CI: 0.02 – 0.9) work overload compared with frequent overload, and exercising at least once a week (OR=0.06; CI: 0.01 – 0.5). In conclusion, factors associated with IBD in Vietnam include smoking, passive smoke exposure, work overload frequency, and physical activity.